De Novo Trisomy 1q10q23.3 Mosaicism Causes Microcephaly, Severe Developmental Delay, and Facial Dysmorphic Features but No Cardiac Anomalies. (31st January 2016) - Lo-A-Njoe, Shirley; van der Veken, Lars T.; Vermont, Clementien; Rafael-Croes, Louise; Keizer, Vincent; Hochstenbach, Ron; Knoers, Nine; van Haelst, Mieke M.
Abstract : Proximal duplications of chromosome 1q are rare chromosomal abnormalities. Most patients with this condition present with neurological, urogenital, and congenital heart disease and short life expectancy. Mosaicism for trisomy 1q10q23.3 has only been reported once in the literature. Here we discuss a second case: a girl with a postnatal diagnosis of a de novo pure mosaic trisomy 1q1023.3 who has no urogenital or cardiac anomalies.